Model Pembelajaran Problem Based Learning sebagai Upaya Peningkatan Prestasi Belajar Mata Pelajaran Pendidikan Kewarganegaraan - Fathimah, Diah Nuraini (Revorma: Jurnal Pendidikan dan Pemikiran, 2022)
Learning Pancasila and Citizenship Education in class XI IPA 3 Madrasah Aliyah Negeri 2 Surakarta has problems, including 1) student achievement results are still low 2) not using various learning methods and learning resources, so learning is less interesting and less fun; 3) students tend to be passive when learning takes place; 4) students' understanding of political culture material is still low. The research used classroom action research (CAR) consisting of 2 cycles. The purpose of this study was to improve students' understanding of the subject of political culture and learning achievement of Civics subjects in class XI IPA 3 MAN 2 Surakarta through the Problem Based Learning method. This research was conducted in class XI IPA 3 MAN 2 Surakarta in the academic year 2020/2021 by applying the Problem Based Learning method. Data collection for learning outcomes is done by observing learning activities, observing peers, and writing tests. Validation of this research data using the triangulation method by re-checking with colleagues in order to obtain accurate data. Data analysis in this study used comparative qualitative and quantitative descriptive data analysis. The performance indicator of PPKn MAN 2 Surakarta subjects is getting a score of > 75 and students complete 75% of the total number of students. The research was carried out in two cycles, each cycle consisting of four stages, namely the planning, implementation, observation, and reflection stages. The results of the study showed 1) The students completed Pre-cycle 17 students, increased to 25 students or 83.33% in the first cycle and increased to 31 students or 100% in the second cycle. Unfinished Students: from Pre-cycle 13 students, it decreased to 5 students in Cycle I and decreased to 0 in Cycle II. Highest Value: from Precycle 80, increased to 85 in cycle I and increased again to 90 in Cycle II. The lowest value of the Precycle was 70, remained at 70 in the first cycle, and increased again to 75 in the second cycle. The average value of the Pre-cycle class was 74.33, which increased to 76.33 in the first cycle and increased again to 78.17 in the second cycle. 2) After the application of the problem-based learning model, it can improve from the initial condition to the final condition after the first cycle and continue in the second cycle, there is a significant increase in the understanding of the material understanding of the nature of democracy.